Diagnostic accuracy of spot urinary protein/creatinine ratio for proteinurea in pregnancy induced hypertension - Jan, Sami; Javaid, Chachoo; Firdous, Nighat (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Hypertensive disorders are the most common medical complications of pregnancy with an incidence of 12-22% and are rampant globally. To assess the diagnostic accuracy of spot urinary protein-creatinine ratio keeping 24 hr urinary protein as gold standard in pregnancy induced hypertension. Methods: Spot urinary protein-creatinine ratio was determined in a mid-stream urine sample. 24 hours, urine protein was measured. The correlation between the spot urinary protein-creatinine ratio and 24-hour urine protein amount was done. Sensitivity, specificity, positive predictive value and negative predictive value along with diagnostic accuracy was calculated from data. Results: There was a strong correlation between the spot urinary protein-creatinine ratio and 24-hour urine protein excretion (pearson’s correlation coefficient r = 0.824; P <0.0001). The optimal spot P/C ratio cut off point was 0.33, for 300 mg/24 hours of protein excretion, with sensitivity and specificity of 82.8% and 76.1% respectively. Positive and negative predictive value are 58.8% and 91.5%. Conclusions: Spot urine P/C ratio is an accurate, reliable and steady fast, timesaving test which can be used as an alternative method for evaluation of proteinuria in pregnancy induced hypertension and it can substitute 24 hours urinary protein excretion estimation in clinical practice.